Analysis of slope stability of waste dump in mine - Tiwari P.; Karmakar N.C. (My University, 2025)
During mining of minerals, the uneconomic materials (i.e. wastes or subgrades) are stacked at different places known as waste dumps. The stability of these dumps has been a major concern over the years. The problem becomes increasingly difficult in rainy season due to the increment in unstable forces. In the present study, the slope stability analysis for the waste dump of an iron ore mine has been carried out. Geotechnical parameters have been used to assess the effect on stability of waste dump. This paper examines the effect of phreatic surface and tension cracks on the factor of safety of rock slopes through the application of 'limit equilibrium analysis'. The 'factor of safety' of the dump section is calculated and analysed using 'Slide software'.